2016
DOI: 10.1007/978-1-4939-3804-9_9
|View full text |Cite
|
Sign up to set email alerts
|

Human Primary Keratinocytes as a Tool for the Analysis of Caspase-1-Dependent Unconventional Protein Secretion

Abstract: Inflammasomes comprise a group of protein complexes, which activate the protease caspase-1 upon sensing a variety of stress factors. Active caspase-1 in turn cleaves and thereby activates the pro-inflammatory cytokines prointerleukin (IL)-1β and -18, and induces unconventional protein secretion (UPS) of mature IL-1β, IL-18, as well as of many other proteins involved in and required for induction of inflammation. Human primary keratinocytes (HPKs) represent epithelial cells able to activate caspase-1 in an infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…34 As noted, release of Caspase-1 through canonical immune pathways results in upregulation of critical inflammatory cytokines such as IL-1β, IL-18, but Caspase-1 can also cleave Pro-IL-1α and Pro-IL-33 through non-canonical immune pathways. 35 Regardless of the pathway, expression of Caspase-1 is linked directly to formation and activation of NLRP Inflammasomes. If the injured cells are creating Caspase-1, it is via an inflammasome-mediated pathway.…”
Section: Caspase-1: a Measure Of Nlrp Inflammasome Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…34 As noted, release of Caspase-1 through canonical immune pathways results in upregulation of critical inflammatory cytokines such as IL-1β, IL-18, but Caspase-1 can also cleave Pro-IL-1α and Pro-IL-33 through non-canonical immune pathways. 35 Regardless of the pathway, expression of Caspase-1 is linked directly to formation and activation of NLRP Inflammasomes. If the injured cells are creating Caspase-1, it is via an inflammasome-mediated pathway.…”
Section: Caspase-1: a Measure Of Nlrp Inflammasome Activationmentioning
confidence: 99%
“…If the injured cells are creating Caspase-1, it is via an inflammasome-mediated pathway. 35 In 2017, O'Brien et al, reported on a new bioluminescence assay that directly detects the release of ACasp-1 from NLRP inflammasomes. 36 Activation of the NLRP inflammasomes can occur via various agonists such as UV energy or chemical initiators.…”
Section: Caspase-1: a Measure Of Nlrp Inflammasome Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…week with 2 mg/ml puromycin. Freshly isolated HPK were cultured in complete keratinocyte medium as described previously (Strittmatter et al, 2016a), transduced for 24 hours and selected for 2 passages with 5 mg/ml puromycin.…”
Section: Crispr/cas9 Gene Deletionmentioning
confidence: 99%
“…Hair follicles were collected from patients at least 6 months after resolution of the ADR. Hair follicle extremities containing outer root sheath were cut, washed in complete keratinocyte medium (Strittmatter et al, 2016), and incubated for 3 minutes in 1 mg/ml Dispase II (Roche, Rotkreuz, Switzerland), followed by three washing steps in medium. The hair was then plated on J2 feeder cells in complete medium and cultured until small colonies of keratinocytes became visible.…”
Section: Primary Keratinocyte Culturementioning
confidence: 99%